Definition of the basic geometric parameters of a carousel type turbine its technological solution (International Journal of Mathematics and Physics, 2019)
Abstract. In the last 10-15 years, the use of wind energy has been developing rapidly. To date, more than 20,000 wind power units have been installed in the world, the total capacity of which exceeds several MW. Kazakhstan has significant resources of wind energy. The most known in this respect are the resources of the Dzungar Gate and Shelek Complex, located in the Almaty region (Kazakhstan). Their possibilities for use in the generation of electric power of air flows are unique.In this paper, the main calculations for determining the influence of the design characteristics of the Darrieus wind turbine on its energy efficiency are presented. The dependence of the maximum coefficient of wind energy use of vertical axle wind wheels on the number of blades at a constant filling factor σ, on the number of blades at their constant width, on the lengthening of the blade λ is studied. Based on these results, design characteristics for a rotor with a power of 1 kW are determined, and a diagram of the wind turbine which can provide thermal protection of the wind turbine by using natural ventilation of warm air inside the rotating elements of the windmill arising from centrifugal forces is also given.And another way of solving the technological problem is proposed. Renounce a long rotating shaft and replace it with a short axis, on which two bearings will rotate with a wind wheel attached to them. Application of the proposed design of the wind farm will simplify the manufacturing technology.Key words: wind turbine, Darrieus, aero dynamical characteristics, natural ventilation, geometrical parameters